Evaluation of the Effects of Topical Application of Chlorhexidine, Ozone, and Metronidazole on Palatal Wound Healing: A Histopathological Study - Acikan, Izzet; Sayeste, Erjeng; Bozoglan, Alihan; Artas, Gokhan; Isayev, Abulfaz; Kirtay, Mustafa; Icen, Veysel (Lippincott Williams & Wilkins, 2022)
This study aimed to evaluate the effects of chlorhexidine, metronidazole, and ozone application on the healing of palatal wounds in diabetic rats. A defect in the form of a 4 mm-diameter wound was created on the palatal mucosa of 84 adult female Wistar albino rats, which were randomly divided into 4 groups: control, chlorhexidine, metronidazole, and ozone groups. The animals were euthanized after 3, 6, and 10 days, and wound closure was histologically assessed. On day 3, polymorphonuclear leukocytes were significantly higher in the control group than in the chlorhexidine and ozone groups (P < 0.05). Fibrosis was higher in the ozone group than in the control and chlorhexidine groups (P < 0.05). Vascular endothelial growth factor was higher in the metronidazole and ozone groups than in the control group (P< 0.05). On day 6, the quantity of polymorphonuclear leukocytes was higher in the control, metronidazole, and chlorhexidine groups than in the ozone group (P < 0.05). Vascular endothelial growth factor was higher in the ozone group than in the control, chlorhexidine, and metronidazole groups (P < 0.05). On day 10, Vascular endothelial growth factor was higher in the control, chlorhexidine, and metronidazole groups than in the ozone group (P < 0.05). The authors concluded that the use of chlorhexidine, ozone, and metronidazole pastes resulted in enhanced wound healing, as determined histologically. The authors suggest that ozone supplementation can be an alternative therapy to chlorhexidine in impaired wound healing in diabetes mellitus.
Keywords: Chlorhexidine; metronidazole; oral mucosa; ozone; palatinal mucosa; wound healing